2017
DOI: 10.13005/ojc/330420
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Assessment of Organotin(IV) (2-Metoxyethyl) Methyldithiocarbamate Compounds in Human Leukemia Cell Lines

Abstract: Dibutyltin(IV) (2-methoxyethyl) methyldithiocarbamate (Compound 1) and tricyclohexyltin(IV) (2-methoxyethyl) methyldithiocarbamate (Compound 2) were used to evaluate their cytotoxicity against three human leukemic cell lines namely Jurkat E6.1, K562, and HL-60. The cytotoxicity of these compounds was assessed using MTT assay for treatment duration of 24 hours. The morphological changes were also observed upon the induction of these compounds with the IC 50 value for 24 hours. Both compounds demonstrated high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The value of IC 50 produced by the organotin(IV) compounds in their study ranged between 0.4-1.3 µM while doxorubicin caused a cytotoxic effect at 0.1 µM. Another study done by Kamaludin et al [11] showed that organotin(IV) (2-metoxyethyl) methyldithiocarbamate compound was able to produce a potent cytotoxic effect on several human leukemia cell lines. As for the HL-60 (acute promyelocytic leukemia) cell line, the IC 50 values of compounds that cause cytotoxic effects are in the range of 0.06-0.18 µM, while for the Jurkat E6.1, the range was 0.14-1.30 µM.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The value of IC 50 produced by the organotin(IV) compounds in their study ranged between 0.4-1.3 µM while doxorubicin caused a cytotoxic effect at 0.1 µM. Another study done by Kamaludin et al [11] showed that organotin(IV) (2-metoxyethyl) methyldithiocarbamate compound was able to produce a potent cytotoxic effect on several human leukemia cell lines. As for the HL-60 (acute promyelocytic leukemia) cell line, the IC 50 values of compounds that cause cytotoxic effects are in the range of 0.06-0.18 µM, while for the Jurkat E6.1, the range was 0.14-1.30 µM.…”
Section: Discussionmentioning
confidence: 87%
“…Organotin compounds are tin (Sn)-based compounds, and have been widely used in industry as components of pesticides, fungicides, bactericides, and as plastic stabilizers [9]. Numerous research has also been conducted to investigate their biological activities, including antitumor properties and mechanisms of action against solid and non-solid cancer cells as part of the development process of new anticancer drugs [10][11][12]. Moreover, different toxicities are displayed depending on the number and nature of functional groups attached to the tin atom [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers in the same area stated that this compound has a high potential to be an anticancer agent against cell lines because its IC50 is less than 1 μm. The data can be strengthened by most studies conducted on organotin compounds against various types of tumor cells that proved these compounds are useful as antitumor agents (Amir et al, 2014;Awang et al, 2011;Gleeson et al, 2008;Kamaludin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further studies related to the treatment for ALL need to be conducted to overcome the issue of resistance that occurs in the current treatments. According to Kamaludin et al [4], current treatments can lead to treatment failure and cancer progression. Therefore, there is a need for new drugs that can act as effective chemotherapeutic agents and do not give side-effects on patients.…”
Section: Introductionmentioning
confidence: 99%